The efficacy of lapatinib in patients with metastatic HER2 positive breast cancer who received prior therapy with monoclonal antibodies and antibody-drug conjugate: a single institutional experience. (19th May 2022) - Kolarov Bjelobrk, Ivana; Radic, Jelena; Trifunovic, Jasna; Pesic, Jasna; Vidovic, Vladimir; Vranjkovic, Bojana; Petrovic, Nemanja; Andrejic Visnjic, Bojana
Abstract: The choice of the anti-HER2 agent depends on country-specific availability, the specific, previously administered anti-HER2 therapy and the relapse-free interval, although there is not much published data on the use of lapatinib after progression on pertuzumab and/or T-DM1. The aim of this research is to determine efficacy of lapatinib in this setting. This research included 111 patients with metastatic HER2 positive breast cancer who received lapatinib with capecitabine at The Oncology Institute of Vojvodina. Lapatinib was given to 83 patients after trastuzumab without prior exposure to pertuzumab or T-DM1 while 28 patients received lapatinib after prior exposure to trastuzumab, pertuzumab and/or T-DM1. In order to determine efficacy of lapatinib in both groups, we measured progression free survival (PFS) and overall survival (OS), as well as by subsets: hormonal status (ER-positive and/or PR-positive tumours versus ER-negative and PR-negative tumours), the number of positive axillary lymph nodes (four or more positive axillary lymph nodes versus less than four positive axillary lymph nodes), marker of proliferation (Ki-67 ≥ 30 versus Ki-67 < 30), disease free interval (metastatic recurrence ≤ 1 year after initial diagnosis versus metastatic recurrence > 1 year after initial diagnosis or de novo metastatic disease. Median PFS was 5.6 months (95% CI 4.6–6.6) in the group of patients who received lapatinib after prior exposure to trastuzumab, pertuzumab and/or T-DM 1 and 7.4 months (95% CI 6.1–10.2) in the group of patients who received lapatinib after trastuzumab (HR, 0.79; 95% CI 0.61–0.98; P = 0.09). The patients with negative prognostic factors such as hormone receptor negativity, more than four positive axillary lymph nodes, marker of proliferation Ki 67 ≥ 30 and metastatic recurrence ≤ 1 year after initial diagnosis, had a similar PFS, regardless of receiving lapatinib after prior exposure to trastuzumab, pertuzumab and/or T-DM1 or without prior exposure. Median OS was 10.1 months (95% CI 8.6-NR) in the group that received lapatinib after exposure to trastuzumab, pertuzumab and/or T-DM1 and 16.3 months (95% CI 14.4–20.2) in the group of patients who received lapatinib after trastuzumab (HR, 0.76; 95% CI, 0.59–0.94; P = 0.04). Patients with negative prognostic factors such as hormone receptor negativity, more than four positive axillary lymph nodes and marker of proliferation Ki 67 ≥ 30, had no distinctly worse OS, regardless of receiving lapatinib after prior exposure to trastuzumab, pertuzumab and/or T-DM1 or without prior exposure. Lapatinib with capecitabine is an effective therapeutic option, especially in patients with negative prognostic factors, who have received prior chemotherapy, trastuzumab, pertuzumab, T-DM1 and remains an acceptable option for HER2 positive metastatic breast cancer until the novel drugs are approved in developing countries.